WASp Is Crucial for the Unique Architecture of the Immunological Synapse in Germinal Center B-Cells - Li, Yanan; Bhanja, Anshuman; Upadhyaya, Arpita; Zhao, Xiaodong; Song, Wenxia (Frontiers in Cell and Developmental Biology, 2021)
B-cells undergo somatic hypermutation and affinity maturation in germinal centers. Somatic hypermutated germinal center B-cells (GCBs) compete to engage with and capture antigens on follicular dendritic cells. Recent studies show that when encountering membrane antigens, GCBs generate actin-rich pod-like structures with B-cell receptor (BCR) microclusters to facilitate affinity discrimination. While deficiencies in actin regulators, including the Wiskott-Aldrich syndrome protein (WASp), cause B-cell affinity maturation defects, the mechanism by which actin regulates BCR signaling in GBCs is not fully understood. Using WASp knockout (WKO) mice that express Lifeact-GFP and live-cell total internal reflection fluorescence imaging, this study examined the role of WASp-mediated branched actin polymerization in the GCB immunological synapse. After rapid spreading on antigen-coated planar lipid bilayers, GCBs formed microclusters of phosphorylated BCRs and proximal signaling molecules at the center and the outer edge of the contact zone. The centralized signaling clusters localized at actin-rich GCB membrane protrusions. WKO reduced the centralized micro-signaling clusters by decreasing the number and stability of F-actin foci supporting GCB membrane protrusions. The actin structures that support the spreading membrane also appeared less frequently and regularly in WKO than in WT GCBs, which led to reductions in both the level and rate of GCB spreading and antigen gathering. Our results reveal essential roles for WASp in the generation and maintenance of unique structures for GCB immunological synapses.